Clade I TGACG-Motif Binding Basic Leucine Zipper Transcription Factors Mediate BLADE-ON-PETIOLE-Dependent Regulation of Development - Wang, Ying (Plant Physiol, 2019)
Lateral organs formed by the shoot apical meristem (SAM) are separated from surrounding stem cells by regions of low growth called boundaries. Arabidopsis (Arabidopsis thaliana) BLADE-ON-PETIOLE1 (BOP1) and BOP2 represent a class of genes important for boundary patterning in land plants. Members of this family lack a DNA-binding domain and interact with TGACG-motif binding (TGA) basic Leu zipper (bZIP) transcription factors for recruitment to DNA. Here, we show that clade I bZIP transcription factors TGA1 and TGA4, previously associated with plant defense, are essential cofactors in BOP-dependent regulation of development. TGA1 and TGA4 are expressed at organ boundaries and function in the same genetic pathways as BOP1 and BOP2 required for SAM maintenance, flowering, and inflorescence architecture. Further, we show that clade I TGAs interact constitutively with BOP1 and BOP2, contributing to activation of ARABIDOPSIS THALIANA HOMEOBOX GENE1, which is needed for boundary establishment. These studies expand the functional repertoire of clade I TGA factors in development and defense.